(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study aims to test the long and short term relationship between tax revenues and investment in Syria, so it was tested the relationship between the types of taxes (income, profits and capital gains taxes, salary and wages taxes, good and services taxes) and both public and private investment for the period (2000-2019), and then tested the relationship between tax revenues and sectoral investment (agricultural, industrial, service) during the period (1975-2019), and showing the impact of the Syrian crisis on the nature of this relationship. The Bound test approach, or what is known as Auto Regressive Distributed Lag (ARDL), was applied to determine the nature of the relation in long and short term. The result showed a positive long and short term relationship between income, profits and capital gains taxes, salary and wages taxes and public investment. There is a negative impact of the Syrian crisis on the nature of this relationship. There is a negative long and short term relationship between salary and wages taxes and privet investments, and this relationship is positive between goods and services taxes and privet investments, and there is a negative impact of the Syrian crisis on the nature of this relationship. There is a positive long and short term relationship between tax revenues and each of the investment in the industrial and service sector, and there is no impact of the Syrian crisis on the nature of this relationship.